Rating Agencies: An Experimental Analysis of their Remuneration Model - Christoph Bühren; Marco Pleßner (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Does it matter who pays for ratings? Yes, but not for the rating agencies' behavior. These are the findings of our experiment where we analyze the effect of the remuneration model of rating agencies on their assessments as well as on investors' and issuers' behavior. First, we find that rating agencies' assessments are comparable whether the agency is (partially) paid by issuers, investors, or solely by the experimenter. Issuers, on the other hand, more often do not return investor's trust when they or investors pay for ratings. Further, investors more often act according to the agencies' recommendations when they have to pay for this information.
Keywords: 330